Cell polarity in plants: the Yin and Yang of cellular functions - Qi, Jiyan; Greb, Thomas (Current opinion in plant biology, 2017)
Spatial organization is fundamental for the performance of living organisms and is reflected in a distinct distribution of structures and molecules down to the subcellular level. In particular, eukaryotic cells harbor a vast range of possibilities for distributing organelles, the cytoskeleton or the extracellular matrix in an active and highly regulated manner. An asymmetric or polar distribution is rather the rule than the exception and often reflects a particular position or orientation of a cell within a multicellular body. Here, we highlight recent insights into the regulation of cell polarity in plants and reveal the interactive nature of underlying molecular processes.